ARIMA-GARCH Markov switching method for forecasting the share price of PT. Bank Rakyat Indonesia (Persero) Tbk. - Afida, Hilda Nurlaila; Ahdika, Atina (Universitas Islam Negeri Raden Intan Lampung, 2024)
Shares are financial instruments that represent a small ownership in a company and give the holder the right to receive dividends and participate in the company’s decisions. The Covid-19 pandemic is also believed to have a major impact on the world stock market, so it is also important to analyze stock price fluctuations before and after the outbreak. One of the suitable methods for predicting stock price volatility is ARIMA-GARCH Markov Switching. The data used is secondary data from PT. Bank Rakyat Indonesia (PERSERO) Tbk. From January 2, 2019 to November 30, 2023. PT stock price data forecast. Bank Rakyat Indonesia (PERSERO) Tbk. Using ARIMA-GARCH Markov Switching method, the best model is ARIMA(2,1,2) GARCH(1,1) and the forecast value obtained is 5280.935; 5275.403; 5276.776; 5279.255; 5275,760 for 5 periods and divided into 2 regimes, namely the first regime with data that has low volatility and the second regime with data that has high volatility.